Tumor detection with transoral use of flexible endoscopy for unknown primary head and neck cancer. Issue 5 (18th September 2021) - Ebisumoto, Koji; Sakai, Akihiro; Maki, Daisuke; Robinson, Kevin; Murakami, Tomoaki; Iijima, Hiroaki; Yamauchi, Mayu; Saito, Kosuke; Watanabe, Takane; Okami, Kenji
Abstract: Objectives: With the advent of new optical technologies, early pharyngolaryngeal cancerous lesions can be better visualized. Although the conventional transnasal approach offers great views of the hypopharynx and larynx, the visualization of the oropharynx and palatine tonsils is limited. Through the transoral insertion of a flexible video‐laryngoscope, direct views of the oropharynx and oral cavity can be obtained. Thus, transoral examination may contribute to primary detection of cancers of unknown primary (CUP). Methods: Eighty‐five CUP patients from Tokai University were included retrospectively in this study, from 2006 to 2017. Starting in 2010, we employed the transoral examination in addition to our conventional method. The primary detection rates were compared before and after 2010. Oropharyngeal primaries were further analyzed for tumor subsite and p16 status. Results: The overall primary detection rate did not improve with the addition of transoral examination. However, greater numbers of oropharyngeal primaries were detected. The oropharyngeal lesions detected by transoral examination were mainly p16 positive, located on the palatine tonsil. Conclusion: Transoral examination is a noninvasive, easy method to adopt in an outpatient setting, and a promising technique to improve tumor detection in this era of human papillomavirus‐associated head and neck cancers. Level of Evidence: 3.